A framework design to develop integrated data system for smart e-government based on big data technology - Dzikrullah, Fahmi; Rinjani, Muhammad Angga (Bulletin of Social Informatics Theory and Application, 2017)
The rapid development of information communication and technology (ICT) in the field of governance or public service has shifted from the age of information to the age of data. The public sector is becoming increasingly aware of the potential value of data, where governments generate and collect large quantities of data (volume), rapid growth data (velocity) and various type of data (variety) through their services. Meanwhile, the government agencies keep constructing the various database, information system or application with different data sources and platform. Therefore, the interoperability has become the important requirements in electronic Government (e-Government) infrastructure that progresses towards higher levels of integration among government levels and branches. In this paper, we proposed a framework design for the development of Integrated Data System for e-Government that we call Smart e-Government, which integrates traditional information systems that is combined with an intelligent system based on big data technology. With this system, the government agencies could provide services environment with greater ease and deliver public value through open government data initiatives in a Smart e-Government context. Moreover, this would also be very useful for the government executives to monitor public services which are increasingly prestige, institutional transparency, as well as accountability. Such integration is to improve the quality of public services through information technology.